Environmental Monitoring of Volatile Organic Compounds Using Silica Gel, Zeolite and Activated Charcoal. Issue 1656 (21st August 2014) - McGath, Molly; McCarthy, Blythe; Bosworth, Jenifer
ABSTRACT: Volatile organic compounds (VOCs) can be hazardous to human health and can negatively impact the long-term stability of art objects. This research evaluated the VOC adsorbent properties of three materials commonly used in museums as humidity regulating or air filtering agents. Silica gel, activated charcoal, and zeolite powder, materials often placed in proximity to art objects, were analyzed using Thermal Desorption GC-MS to qualitatively identify adsorbed VOC's from model environments. This research compared the adsorbing capabilities of these materials with a solid-phase micro-extraction (SPME) carboxen/polydimethyl siloxane fiber to frame their adsorbing powers. It was found that different adsorbents have very different ranges of adsorption for the chemicals tested. Silica gel powder and zeolite powder have the greatest sensitivity for acetic acid over a 24 hour exposure period. Zeolite powder and activated charcoal were more sensitive for identification of naphthalene. Silica gel powder proved to be the most sensitive adsorbent overall. This research discovered that the methods used to condition silica gel pellets for reuse need to be re-examined in light of fact they trap VOC's, especially as it was observed that VOC's desorb from the silica gel pellets under ambient conditions.